Once-only sigmoidoscopy in colorectal cancer screening: follow-up findings of the Italian Randomized Controlled Trial--SCORE - Segnan, Nereo; Armaroli, Paola; Bonelli, Luigina; Risio, Mauro; Sciallero, Stefania; Zappa, Marco; Andreoni, Bruno; Arrigoni, Arrigo; Bisanti, Luigi; Casella, Claudia; Crosta, Cristiano; Falcini, Fabio; et al. (JNCI : Journal of the National Cancer Institute, 2011)
A single flexible sigmoidoscopy at around the age of 60 years has been proposed as an effective strategy for colorectal cancer (CRC) screening. We conducted a randomized controlled trial to evaluate the effect of flexible sigmoidoscopy screening on CRC incidence and mortality. A questionnaire to assess the eligibility and interest in screening was mailed to 236,568 men and women, aged 55-64 years, who were randomly selected from six trial centers in Italy. Of the 56,532 respondents, interested and eligible subjects were randomly assigned to the intervention group (invitation for flexible sigmoidoscopy; n = 17,148) or the control group (no further contact; n = 17,144), between June 14, 1995, and May 10, 1999. Flexible sigmoidoscopy was performed on 9911 subjects. Intention-to-treat and per-protocol analyses were performed to compare the CRC incidence and mortality rates in the intervention and control groups. Per-protocol analysis was adjusted for noncompliance. A total of 34,272 subjects (17,136 in each group) were included in the follow-up analysis. The median follow-up period was 10.5 years for incidence and 11.4 years for mortality; 251 subjects were diagnosed with CRC in the intervention group and 306 in the control group. Overall incidence rates in the intervention and control groups were 144.11 and 176.43, respectively, per 100,000 person-years. CRC-related death was noted in 65 subjects in the intervention group and 83 subjects in the control group. Mortality rates in the intervention and control groups were 34.66 and 44.45, respectively, per 100,000 person-years. In the intention-to-treat analysis, the rate of CRC incidence was statistically significantly reduced in the intervention group by 18% (rate ratio [RR] = 0.82, 95% confidence interval [CI] = 0.69 to 0.96), and the mortality rate was non-statistically significantly reduced by 22% (RR = 0.78; 95% CI = 0.56 to 1.08) compared with the control group. In the per-protocol analysis, both CRC incidence and mortality rates were statistically significantly reduced among the screened subjects; CRC incidence was reduced by 31% (RR = 0.69; 95% CI = 0.56 to 0.86) and mortality was reduced by 38% (RR = 0.62; 95% CI = 0.40 to 0.96) compared with the control group. A single flexible sigmoidoscopy screening between ages 55 and 64 years was associated with a substantial reduction of CRC incidence and mortality.